2005
DOI: 10.1002/elan.200403270
|View full text |Cite
|
Sign up to set email alerts
|

Stripping Analysis at Bismuth Electrodes: A Review

Abstract: For many years mercury electrodes were the transducer of choice in stripping voltammetry of trace metals owing to their high sensitivity, reproducibility, and renewability. However, because of the toxicity of mercury, alternative (environmentally friendly) electrode materials are highly desired for both centralized and field applications. Recently introduced bismuth electrodes offer a very attractive alternative to commonly used mercury electrodes. Such electrodes display well-defined, undistorted and highly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
388
0
20

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(409 citation statements)
references
References 33 publications
1
388
0
20
Order By: Relevance
“…Bismuth which knew as an environmentally friendly material has received significant attention as an alternative to commonly used toxic mercury in electroanalysis. A wide variety of bismuth-based electrodes, sensors, and detectors of various types, configurations, or constructions had been reported by many researchers [4]. Among them, bismuth film electrodes were mostly used (BiFE) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth which knew as an environmentally friendly material has received significant attention as an alternative to commonly used toxic mercury in electroanalysis. A wide variety of bismuth-based electrodes, sensors, and detectors of various types, configurations, or constructions had been reported by many researchers [4]. Among them, bismuth film electrodes were mostly used (BiFE) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the drawbacks of mercury electrode, such as toxicity, difficulties in the handling and storage [19], chemically modified electrodes have been developed for iron determination. Among the various modified electrodes, the bismuth-based electrodes seem to be the most promising alternatives owing to their lower mercury toxicity, ability to form alloys with metal and considerably sensitive voltammetric detection.…”
Section: Introductionmentioning
confidence: 99%
“…When metals are deposited in solid form on electrodes, the dissolution signals are often more complicate (multi peaks) because of the different activities of different crystallographic surface planes. However, in recent years, it has been shown that bismuth film electrodes (on glassy carbon) are an attractive alternative to mercury electrodes [23].…”
Section: Anodic Stripping Voltammetry (Asv)mentioning
confidence: 99%